Risk, Trust, and Flawed Assumptions: Vaccine Hesitancy During the COVID-19 Pandemic - Omid V. Ebrahimi; Omid V. Ebrahimi; Miriam S. Johnson; Sara Ebling; Ole Myklebust Amundsen; Øyvind Halsøy; Asle Hoffart; Asle Hoffart; Nora Skjerdingstad; Sverre Urnes Johnson; Sverre Urnes Johnson (Frontiers Media S.A., 2021)
Background: The pace at which the present pandemic and future public health crises involving viral infections are eradicated heavily depends on the availability and routine implementation of vaccines. This process is further affected by a willingness to vaccinate, embedded in the phenomenon of vaccine hesitancy. The World Health Organization has listed vaccine hesitancy among the greatest threats to global health, calling for research to identify the factors associated with this phenomenon.Methods: The present cross-sectional study seeks to investigate the psychological, contextual, and sociodemographic factors associated with vaccination hesitancy in a large sample of the adult population. 4,571 Norwegian adults were recruited through an online survey between January 23 to February 2, 2021. Subgroup analyzes and multiple logistic regression was utilized to identify the covariates of vaccine hesitancy.Results: Several subgroups hesitant toward vaccination were identified, including males, rural residents, and parents with children below 18 years of age. No differences were found between natives and non-natives, across education or age groups. Individuals preferring unmonitored media platforms (e.g., information from peers, social media, online forums, and blogs) more frequently reported hesitance toward vaccination than those relying on information obtainment from source-verified platforms. Perceived risk of vaccination, belief in the superiority of natural immunity, fear concerning significant others being infected by the virus, and trust in health officials' dissemination of vaccine-related information were identified as key variables related to vaccine hesitancy.Conclusion: Given the heterogeneous range of variables associated with vaccine hesitancy, additional strategies to eradicate vaccination fears are called for aside from campaigns targeting the spread of false information. Responding to affective reactions in addition to involving other community leaders besides government and health officials present promising approaches that may aid in combating vaccination hesitation.